Paleodiet and niche breadth in Middle Miocene rodents and ungulates from northern South America revealed through stable isotope analyses - Laura E. Arias-Concha; Michael J. Ziegler; Patrick Roberts; Francisco J. Urrea-Barreto; Darin Croft; Siobhán B. Cooke; Catalina Zorro; Jana Ilgner; Erin Scott; Andres Vanegas-Vanegas; Cesar Augusto Perdomo; Andrés Link (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Spawning habitat selection and behavioural repeatability of stocked Walleye (Sander vitreus) in Hamilton Harbour - Paul A. Bzonek; Melanie V. Croft-White; David T. Reddick; Nicole A. Turner; M. Cole MacLeod; Steven J. Cooke; Jill L. Brooks; Caleb T. Hasler; Jonathan D. Midwood (Aquatic Sciences, 2026)

On‐Farm Demonstration and Economic Evaluation of an IoT Sensing System for Irrigation Management in South Carolina - J. O. Payero; U. Sekaran; D. B. Turner; S. Selvalakshmi; M. W. Marshall; N. Smith; J. Croft; A. S. Hill; R. Hitchcock‐Davis (Irrigation and Drainage, 2026)
Irrigation can strongly influence agricultural productivity and sustainability. While sensor‐based irrigation has the potential to improve yield, reduce input costs and enhance resource‐use efficiency, its adoption in commercial agriculture remains limited. This study evaluated and demonstrated the performance of an IoT soil water monitoring system and the effects of sensor‐based irrigation on crop yield and economic returns in commercial farms in South Carolina. Field demonstrations were conducted across 18 site‐year observations (six farms annually from 2020–2022) under centre pivot systems. The centre pivot fields for each farm were divided into sensor fields and companion fields. The sensor fields used soil water potential (SWP) data from sensors installed at multiple depths to guide irrigation, while irrigation in the companion field followed farmers' preferred practices. Data collected from each site included irrigation applied, pumping characteristics, energy use, yield and economic returns. The IoT monitoring system reliably collected and transmitted data across all locations and years. Despite variability, the sensor fields achieved average increases of 11% in yield and 12% in net economic return compared with companion fields. These results indicate that sensor‐based irrigation improves water management and profitability under commercial conditions, supporting broader adoption of these technologies.

Social equity indicators for a Blue Economy: Guidelines for application - A.M. Cisneros-Montemayor; H. Breakey; S. Bossier; F. Croft; I. Issifu; J. Keefer; G.G. Singh; M. Voyer; Y. Ota (Marine Policy, 2025)

Methodological considerations for studying spectral-plant diversity relationships - Christine I.B. Wallis; Anna L. Crofts; Robert Jackisch; Shan Kothari; Guillaume Tougas; J. Pablo Arroyo-Mora; Paul Hacker; Nicholas Coops; Margaret Kalacska; Etienne Laliberté; Mark Vellend (Remote Sensing of Environment, 2025)

Exposure to radiofrequency electromagnetic fields and IARC carcinogen assessment: Risk of Bias preliminary literature assessment for 10 key characteristics of human carcinogens - Myrtill Simkó; Michael H. Repacholi; Kenneth R. Foster; Mats-Olof Mattsson; Rodney J. Croft; Maria Rosaria Scarfi; Vijayalaxmi (Mutation Research - Reviews in Mutation Research, 2025)

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Effects of fine-scale changes in resource access and social stability on the sociality of foraging flocks of wild birds - Camille A. Troisi; Josh A. Firth; Sam J. Crofts; Gabrielle L. Davidson; Michael S. Reichert; John L. Quinn (Animal Behaviour, 2025)

Source specific fine particles and rates of asthma and COPD healthcare encounters pre- and post-implementation of the Tier 3 vehicle emissions control regulations - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; Philip K. Hopke; David Q. Rich (Journal of Hazardous Materials, 2025)

Diversity of movement patterns of Longnose Gar tracked in coastal waters of western Lake Ontario - Melanie V. Croft-White; Sarah M. Larocque; David T. Reddick; Paul D. Smith; Steven J. Cooke; Jonathan D. Midwood (Environmental Biology of Fishes, 2024)
Understanding the spatial ecology of fish is critical for effective conservation and management. Gar (Lepisosteidae spp.) are an ancient lineage of freshwater fishes that have long been thought of as having high site fidelity with limited large-scale movements. We acoustically tagged Longnose Gar ( L. osseus ) in a large freshwater embayment (Hamilton Harbour) and tracked the movements of 12 individuals within this system and throughout the coastal waters of Lake Ontario for up to 4 years. Three distinct movement patterns were observed: migrants ( N = 7), which moved throughout much of western Lake Ontario and had a maximum displacement of 184 km (linear distance); residents ( N = 3), which remained in or near the original tagging location (an industrial slip with year-round warmwater outfall); and sporadic migrants ( N = 2), which showed both migratory and resident behavioural patterns in different years. Seasonally, gar were most active during the summer and then fall, with more restricted home ranges and movements during winter suggestive of more quiescent behaviour. This study represents the first use of acoustic telemetry to track Longnose Gar movements year-round in a large lake and confirmed that a majority of tracked fishes make large-scale movements in Lake Ontario. Such results reframe the presumption that gar are more resident fishes with restricted space use.

Modelling the continuum of macrophage phenotypes and their role in inflammation - Suliman Almansour; Joanne L. Dunster; Jonathan J. Crofts; Martin R. Nelson (Mathematical Biosciences, 2024)

PM2.5 and its components and respiratory disease healthcare encounters – Unanticipated increased exposure-response relationships in recent years after environmental policies - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Philip K. Hopke; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; David Q. Rich (Environmental Pollution, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Fitness consequences of population bottlenecks in an invasive blowfly - Lilly Croft; Paige Matheson; Nathan J. Butterworth; Angela McGaughran (Molecular Ecology, 2024)
Invasive species often undergo demographic bottlenecks that cause a decrease in genetic diversity and associated reductions in population fitness. Despite this, they manage to thrive in novel environments. Investigating the effects of inbreeding and genetic bottlenecks on population fitness for invasive species is, therefore, key to understanding how they may survive in new environments. We used the blowfly Calliphora vicina ( Sciences, Mathématiques et Physique , 1830, 2, 1), which is native to Europe and was introduced to Australia and New Zealand, to examine the effects of genetic diversity on population fitness. We first collected 59 samples from 15 populations across New Zealand and one in Australia, and used 20,501 biallelic SNPs to investigate population genomic diversity, structure and admixture. We then explored the impacts of repeated experimental bottlenecks on population fitness by creating inbred and outbred lines of C. vicina and measuring a variety of fitness traits. In wild‐caught samples, we found low overall genetic diversity, signals of genetic admixture and limited ( C. vicina (when under relaxed selection, as in laboratory settings) may be able to compensate for population bottlenecks even when highly inbred. Our results demonstrate the value of a tractable experimental system for investigating processes that may facilitate or hamper biological invasion.

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Insect seed and cone predation reduces reproductive potential of treeline conifers across northern Canada - Lucas Brehaut; Katie J. A. Goodwin; Kirsten A. Reid; Anna L. Crofts; Ryan K. Danby; Steven D. Mamet; Carissa D. Brown (Journal of Biogeography, 2023)
Aim Altitudinal and latitudinal treeline ecotones have not consistently responded to climate warming in the direction and/or magnitude predicted by climate alone, suggesting that non‐climatic mechanisms (e.g. biotic interactions) also mediate treeline range dynamics. Through a collaborative research approach, we assessed environmental conditions associated with pre‐dispersal insect cone granivory and how this biotic interaction may govern the reproductive potential, and therefore range dynamics, of spruce‐dominated treelines across northern Canada. Location In all, 10 boreal forest treelines, tundra and alpine, from Yukon to Newfoundland and Labrador, Canada. Taxa White spruce ( Picea glauca [Moench] Voss), Black spruce ( Picea mariana [Mill.] B.S.P.), Strobilomyia spp., Megastigmus spp. Methods Treeline sites were assessed for presence and magnitude of pre‐dispersal seed granivory by insects along with viable seed availability. We quantified stand density metrics, organic layer depth and understorey vegetation composition at each location and, subsequently, incorporated those variables into generalized linear mixed models to establish predictors of granivory magnitude and viability of available seed. Results Insect granivory was widespread across sites; however, site‐specific patterns of granivory were associated with increased moss cover and decreased shrub cover and stand density. While all black spruce‐dominated sites exhibited seed viability rates > 50%, the number of seeds produced per cone varied, suggesting that within‐site abiotic conditions and biotic interaction pressures limit successful colonization of novel environments in advance of seed dispersal. Main Conclusions The modelled relationships between granivory, seed viability and environmental conditions represent an essential step towards generalizing how and when biotic interactions across subarctic treelines influence boreal tree range dynamics before seed dispersal. Connections between granivory magnitude and site‐level treeline characteristics (e.g. stand density, understorey vegetation) will provide a more comprehensive understanding of treeline range dynamics under continued climate change.

Potential role of biologgers to automate detection of lame ewes and lambs - KE Lewis; E. Price; DP Croft; LE Green; L. Ozella; C. Cattuto; J. Langford (Applied Animal Behaviour Science, 2023)

Potential for redistribution of post‐moult habitat for Eudyptes penguins in the Southern Ocean under future climate conditions - Cara‐Paige Green; David B. Green; Norman Ratcliffe; David Thompson; Mary‐Anne Lea; Alastair M. M. Baylis; Alexander L. Bond; Charles‐André Bost; Sarah Crofts; Richard J. Cuthbert; Jacob González‐Solís; Kyle W. Morrison; et al. (Global Change Biology, 2023)
Anthropogenic climate change is resulting in spatial redistributions of many species. We assessed the potential effects of climate change on an abundant and widely distributed group of diving birds, Eudyptes penguins, which are the main avian consumers in the Southern Ocean in terms of biomass consumption. Despite their abundance, several of these species have undergone population declines over the past century, potentially due to changing oceanography and prey availability over the important winter months. We used light‐based geolocation tracking data for 485 individuals deployed between 2006 and 2020 across 10 of the major breeding locations for five taxa of Eudyptes penguins. We used boosted regression tree modelling to quantify post‐moult habitat preference for southern rockhopper ( E. chrysocome ), eastern rockhopper ( E. filholi ), northern rockhopper ( E. moseleyi ) and macaroni/royal ( E. chrysolophus and E. schlegeli ) penguins. We then modelled their redistribution under two climate change scenarios, representative concentration pathways RCP4.5 and RCP8.5 (for the end of the century, 2071–2100). As climate forcings differ regionally, we quantified redistribution in the Atlantic, Central Indian, East Indian, West Pacific and East Pacific regions. We found sea surface temperature and sea surface height to be the most important predictors of current habitat for these penguins; physical features that are changing rapidly in the Southern Ocean. Our results indicated that the less severe RCP4.5 would lead to less habitat loss than the more severe RCP8.5. The five taxa of penguin may experience a general poleward redistribution of their preferred habitat, but with contrasting effects in the (i) change in total area of preferred habitat under climate change (ii) according to geographic region and (iii) the species (macaroni/royal vs. rockhopper populations). Our results provide further understanding on the regional impacts and vulnerability of species to climate change.

Remotely sensed carbon content: The role of tree composition and tree diversity - Christine I.B. Wallis; Anna L. Crofts; Deep Inamdar; J. Pablo Arroyo-Mora; Margaret Kalacska; Étienne Laliberté; Mark Vellend (Remote Sensing of Environment, 2023)

High frequency UV–Vis sensors estimate error in riverine dissolved organic carbon load estimates from grab sampling - J. P. Ritson; O. Kennedy-Blundell; J. Croft; M. R. Templeton; C. E. Hawkins; J. M. Clark; M. G. Evans; R. E. Brazier; D. Smith; N. J. D. Graham (Environmental Monitoring and Assessment, 2022)
High frequency ultraviolet – visible (UV–VIS) sensors offer a way of improving dissolved organic carbon (DOC) load estimates in rivers as they can be calibrated to DOC concentration. This is an improvement on periodic grab sampling, or the use of pumped sampling systems which store samples in-field before collection. We hypothesised that the move to high frequency measurements would increase the load estimate based on grab sampling due to systemic under-sampling of high flows. To test our hypotheses, we calibrated two sensors in contrasting catchments (Exe and Bow Brook, UK) against weekly grab sampled DOC measurements and then created an hourly time series of DOC for the two sites. Taking this measurement as a ‘true’ value of DOC load, we simulated 1,000 grab sampling campaigns at weekly, fortnightly and monthly frequency to understand the likely distribution of load and error estimates. We also performed an analysis of daily grab samples collected using a pumped storage sampling system with weekly collection. Our results show that: a) grab sampling systemically underestimates DOC loads and gives positively skewed distributions of results, b) this under-estimation and positive skew decreases with increasing sampling frequency, c) commonly used estimates of error in the load value are also systemically lowered by the oversampling of low, stable flows due to their dependence on the variance in the flow-weighted mean concentration, and d) that pumped storage systems may lead to under-estimation of DOC and over estimation of specific ultra-violet absorbance (SUVA), a proxy for aromaticity, due to biodegradation during storage.

Whole genome resequencing reveals signatures of rapid selection in a virus‐affected commercial fishery - Owen J. Holland; Madeline Toomey; Collin Ahrens; Ary A. Hoffmann; Laurence J. Croft; Craig D. H. Sherman; Adam D. Miller (Molecular Ecology, 2022)
Infectious diseases are recognized as one of the greatest global threats to biodiversity and ecosystem functioning. Consequently, there is a growing urgency to understand the speed at which adaptive phenotypes can evolve and spread in natural populations to inform future management. Here we provide evidence of rapid genomic changes in wild Australian blacklip abalone ( Haliotis rubra ) following a major population crash associated with an infectious disease. Genome scans on H . rubra were performed using pooled whole genome resequencing data from commercial fishing stocks varying in historical exposure to haliotid herpesvirus‐1 (HaHV‐1). Approximately 25,000 single nucleotide polymorphism loci associated with virus exposure were identified, many of which mapped to genes known to contribute to HaHV‐1 immunity in the New Zealand pāua ( Haliotis iris ) and herpesvirus response pathways in haliotids and other animal systems. These findings indicate genetic changes across a single generation in H . rubra fishing stocks decimated by HaHV‐1, with stock recovery potentially determined by rapid evolutionary changes leading to virus resistance. This is a novel example of apparently rapid adaptation in natural populations of a nonmodel marine organism, highlighting the pace at which selection can potentially act to counter disease in wildlife communities.

The effect of age, sex, and resource abundance on patterns of rake markings in resident killer whales ( Orcinus orca ) - Charli Grimes; Lauren J. N. Brent; Michael N. Weiss; Daniel W. Franks; Kenneth C. Balcomb; David K. Ellifrit; Samuel Ellis; Darren P. Croft (Marine Mammal Science, 2022)
Fluctuations in aggressive behavior of group‐living species can reflect social conflict and competition for resources faced by individuals throughout their lifespan and can negatively impact survival and reproduction. In marine mammals, where social interactions are difficult to observe, tooth rake marks can be used as an indicator of received aggression. Using 38 years of photographic data, we quantified the occurrence of tooth rake marks on wild resident killer whales ( Orcinus orca ), examining the effects of age, sex, and prey abundance on rake density. Our analysis revealed sex and age effects, with males exhibiting higher rake density than females and rake density declining significantly with age. Contrary to predictions, we observed an increase in rake density across the population as the abundance of their primary food resource, Chinook salmon ( Oncorhynchus tshawytscha ), increased. These results provide indirect evidence of fluctuations in received aggression from conspecifics across the lifespan of an individual, possibly reflecting changes in patterns of social conflict which may be mediated by resource abundance. Our findings highlight the need for further research to examine the fitness consequences of aggression in killer whales and to understand the proximate mechanisms by which resource abundance influences rates of aggression in the population.

Comparative Endocranial Anatomy, Encephalization, and Phylogeny of Notoungulata (Placentalia, Mammalia) - Fernando A. Perini; Thomas E. Macrini; John J. Flynn; Kanvaly Bamba; Xijun Ni; Darin A. Croft; André R. Wyss (Journal of Mammalian Evolution, 2022)

Acute effects of Δ9-tetrahydrocannabinol and cannabidiol on auditory mismatch negativity - Lisa-Marie Greenwood; Samantha J. Broyd; Hendrika H. van Hell; Juanita Todd; Alison Jones; Robin M. Murray; Rodney J. Croft; Patricia T. Michie; Nadia Solowij (Psychopharmacology, 2022)

Sensory‐based quantification of male colour patterns in Trinidadian guppies reveals no support for parallel phenotypic evolution in multivariate trait space - Lengxob Yong; Darren P. Croft; Jolyon Troscianko; Indar W. Ramnarine; Alastair J. Wilson (Molecular Ecology, 2022)
Parallel evolution, in which independent populations evolve along similar phenotypic trajectories, offers insights into the repeatability of adaptive evolution. Here, we revisit a classic example of parallelism, that of repeated evolution of brighter males in the Trinidadian guppy ( Poecilia reticulata ). In guppies, colonisation of low predation habitats is associated with emergence of ‘more colourful’ phenotypes since predator‐induced viability selection for crypsis weakens while sexual selection by female preference for conspicuousness remains strong. Our study differs from previous investigations in three respects. First, we adopted a multivariate phenotyping approach to characterise parallelism in multitrait space. Second, we used ecologically‐relevant colour traits defined by the visual systems of the two selective agents (i.e., guppy, predatory cichlid). Third, we estimated population genetic structure to test for adaptive (parallel) evolution against a model of neutral phenotypic divergence. We find strong phenotypic differentiation that is inconsistent with a neutral model but very limited support for the predicted pattern of greater conspicuousness at low predation. Effects of predation regime on each trait were in the expected direction, but weak, largely nonsignificant, and explained little among‐population variation. In multitrait space, phenotypic trajectories of lineages colonising low from high predation regimes were not parallel. Our results are consistent with reduced predation risk facilitating adaptive differentiation, potentially by female choice, but suggest that this proceeds in independent directions of multitrait space across lineages. Pool‐sequencing data also revealed SNPs showing greater differentiation than expected under neutrality, among which some are found in genes contributing to colour pattern variation, presenting opportunities for future genetic study.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Head of the Class: John R. Wible’s Transformative Insights Into Mammalian Craniodental Anatomy - Guillermo W. Rougier; Timothy J. Gaudin; Darin A. Croft (Journal of Mammalian Evolution, 2021)

New Chinchillid Rodents (Hystricognathi: Caviomorpha) from Northern Chile and Bolivia Fill a 17-Million-Year Gap in the Pan-Chinchilline Fossil Record - Darin A. Croft; John J. Flynn; André R. Wyss; Reynaldo Charrier; Federico Anaya (Journal of Mammalian Evolution, 2021)

Correction to: Fish composition, but not richness or abundance, differ among Phragmites, Typha, and Schoenoplectus zones during a high-water year - M. V. Croft-White; E. Budgell; C. Jacobs; S. E. Doka; D. T. Reddick; J. Gardner Costa; J. D. Midwood (Hydrobiologia, 2021)

Fish composition, but not richness or abundance, differ among Phragmites, Typha, and Schoenoplectus zones during a high-water year - M. V. Croft-White; E. Budgell; C. Jacobs; S. E. Doka; D. T. Reddick; J. Gardner Costa; J. D. Midwood (Hydrobiologia, 2021)

Characterizing Atmospheric Aerosols off the Atlantic Canadian Coast During C-FOG - Nicole Chisholm; Baban Nagare; Charlotte Wainwright; Ed Creegan; Leyla Salehpoor; Trevor C. VandenBoer; Terry Bullock; Betty Croft; Glen Lesins; Hans Osthoff; H. J. S. Fernando; Rachel Y.-W. Chang (Boundary-Layer Meteorology, 2021)

Wi-fi related radiofrequency electromagnetic fields (RF-EMF): a pilot experimental study of personal exposure and risk perception - Berihun M. Zeleke; Christopher Brzozek; Chhavi R. Bhatt; Michael J. Abramson; Frederik Freudenstein; Rodney J. Croft; Peter Wiedemann; Geza Benke (Journal of Environmental Health Science and Engineering, 2021)
The impact of providing people with an objectively measured personal radiofrequency electromagnetic fields (RF-EMF) exposure information on the risk perception of people is not well understood. We conducted an experimental study, among three groups of participants, to investigate the risk perception of people towards RF-EMF from Wi-Fi sources (ISM 2.4 GHz) by providing participants with either basic text, precautionary information, or a summary of their personal RF-EMF exposure measurement levels. Participants provided with personal RF-EMF exposure measurement information were more confident in protecting themselves from RF-EMF exposure, compared to those provided with only basic information. Nonetheless, neither the exposure perception nor the risk perception of people to Wi-Fi related RF-EMF differed by the type of information provided. The measured Wi-Fi signal levels were far below international exposure limits. Furthermore, self-rated levels of personal RF-EMF exposure perception were not associated with objectively measured RF-EMF exposure levels. Providing people with objectively measured information may help them build confidence in protecting themselves from Wi-Fi related RF-EMF exposure.

Hyperthermia, but not dehydration, alters the electrical activity of the brain - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Nigel A. S. Taylor; Rodney J. Croft (European Journal of Applied Physiology, 2020)

Hyperthermia and dehydration: their independent and combined influences on physiological function during rest and exercise - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Rodney J. Croft; Gregory E. Peoples; Nigel A. S. Taylor (European Journal of Applied Physiology, 2020)

Changes and consistencies in marine and coastal bird numbers on Kidney Island (Falkland Islands) over half a century - P. Catry; T. J. Clark; S. Crofts; A. Stanworth; E. D. Wakefield (Polar Biology, 2019)

Comparative population genomics reveals key barriers to dispersal in Southern Ocean penguins - Gemma V. Clucas; Jane L. Younger; Damian Kao; Louise Emmerson; Colin Southwell; Barbara Wienecke; Alex D. Rogers; Charles‐André Bost; Gary D. Miller; Michael J. Polito; Patrick Lelliott; Jonathan Handley; et al. (Molecular Ecology, 2018)
The mechanisms that determine patterns of species dispersal are important factors in the production and maintenance of biodiversity. Understanding these mechanisms helps to forecast the responses of species to environmental change. Here, we used a comparative framework and genomewide data obtained through RAD ‐Seq to compare the patterns of connectivity among breeding colonies for five penguin species with shared ancestry, overlapping distributions and differing ecological niches, allowing an examination of the intrinsic and extrinsic barriers governing dispersal patterns. Our findings show that at‐sea range and oceanography underlie patterns of dispersal in these penguins. The pelagic niche of emperor ( Aptenodytes forsteri ), king ( A. patagonicus ), Adélie ( Pygoscelis adeliae ) and chinstrap ( P. antarctica ) penguins facilitates gene flow over thousands of kilometres. In contrast, the coastal niche of gentoo penguins ( P. papua ) limits dispersal, resulting in population divergences. Oceanographic fronts also act as dispersal barriers to some extent. We recommend that forecasts of extinction risk incorporate dispersal and that management units are defined by at‐sea range and oceanography in species lacking genetic data.

A numerical simulation of neural fields on curved geometries - R. Martin; D. J. Chappell; N. Chuzhanova; J. J. Crofts (Journal of Computational Neuroscience, 2018)

Do elevated blood levels of omega-3 fatty acids modify effects of particulate air pollutants on fibrinogen? - Daniel Croft; Robert Block; Scott J. Cameron; Kristin Evans; Charles J. Lowenstein; Frederick Ling; Wojciech Zareba; Philip K. Hopke; Mark J. Utell; Sally W. Thurston; Kelly Thevenet-Morrison; David Q. Rich (Air Quality, Atmosphere & Health, 2018)

Effect of dietary nitrate supplementation on thermoregulatory and cardiovascular responses to submaximal cycling in the heat - Georgina L. Kent; Brian Dawson; Gregory R. Cox; Chris R. Abbiss; Kurt J. Smith; Kevin D. Croft; Zi Xiang Lim; Annette Eastwood; Louise M. Burke; Peter Peeling (European Journal of Applied Physiology, 2018)

Daily land use regression estimated woodsmoke and traffic pollution concentrations and the triggering of ST-elevation myocardial infarction: a case-crossover study - David Q. Rich; Mark J. Utell; Daniel P. Croft; Sally W. Thurston; Kelly Thevenet-Morrison; Kristin A. Evans; Frederick S. Ling; Yilin Tian; Philip K. Hopke (Air Quality, Atmosphere & Health, 2018)

Contact networks structured by sex underpin sex‐specific epidemiology of infection - Matthew J. Silk; Nicola L. Weber; Lucy C. Steward; David J. Hodgson; Mike Boots; Darren P. Croft; Richard J. Delahay; Robbie A. McDonald (Ecology Letters, 2018)
Contact networks are fundamental to the transmission of infection and host sex often affects the acquisition and progression of infection. However, the epidemiological impacts of sex‐related variation in animal contact networks have rarely been investigated. We test the hypothesis that sex‐biases in infection are related to variation in multilayer contact networks structured by sex in a population of European badgers Meles meles naturally infected with Mycobacterium bovis . Our key results are that male‐male and between‐sex networks are structured at broader spatial scales than female‐female networks and that in male‐male and between‐sex contact networks, but not female‐female networks, there is a significant relationship between infection and contacts with individuals in other groups. These sex differences in social behaviour may underpin male‐biased acquisition of infection and may result in males being responsible for more between‐group transmission. This highlights the importance of sex‐related variation in host behaviour when managing animal diseases.

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

The independent influences of heat strain and dehydration upon cognition - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Nigel A. S. Taylor; Rodney J. Croft (European Journal of Applied Physiology, 2017)

Sexual response of male Drosophila to honey bee queen mandibular pheromone: implications for genetic studies of social insects - Justin R. Croft; Tom Liu; Alison L. Camiletti; Anne F. Simon; Graham J. Thompson (Journal of Comparative Physiology A, 2017)

Assessment of resistance to root-lesion and root-knot nematodes in Australian hybrid clones of sugarcane and its wild relatives - S. A. Bhuiyan; B. J. Croft; G. R. Stirling; E. Wong; P. Jackson; M. Cox (Australasian Plant Pathology, 2016)

First comprehensive multi-tissue transcriptome of Cherax quadricarinatus (Decapoda: Parastacidae) reveals unexpected diversity of endogenous cellulase - Mun Hua Tan; Han Ming Gan; Huan You Gan; Yin Peng Lee; Larry J. Croft; Mark B. Schultz; Adam D. Miller; Christopher M. Austin (Organisms Diversity & Evolution, 2016)

Social networks in elasmobranchs and teleost fishes - A D M Wilson; D P Croft; J Krause (Fish and Fisheries, 2014)
Over the last decade, there has been an exponential increase in studies using social network analysis to describe the structure of animal societies. In this synthesis, we examine the contribution of social network analysis towards developing our understanding of the social organization of elasmobranchs and teleost fishes. We review and discuss the current state of knowledge of the mechanisms and functions underpinning social network structure in fishes with particular emphasis on cooperation, familiarity, site fidelity, population structure and the welfare of captive populations. We also discuss important methodological issues (e.g. how to identify and mark fish) and highlight new developments in this area of research and their implications for the study of fish behaviour. Finally, we outline promising future research areas for the application of social network analysis to teleost fishes and elasmobranchs.

Characterization of RNA binding protein RBP-P reveals a possible role in rice glutelin gene expression and RNA localization - Kelly A. Doroshenk; Li Tian; Andrew J. Crofts; Toshihiro Kumamaru; Thomas W. Okita (Plant Molecular Biology, 2014)

Efficacy of the fungicide flutriafol for the control of pineapple sett rot of sugarcane in Australia - S. A. Bhuiyan; B. J. Croft; G. R. Tucker (Australasian Plant Pathology, 2014)

Dynamic social networks in guppies (Poecilia reticulata) - Alexander D. M. Wilson; Stefan Krause; Richard James; Darren P. Croft; Indar W. Ramnarine; Karoline K. Borner; Romain J. G. Clement; Jens Krause (Behavioral Ecology and Sociobiology, 2014)

Love thy neighbour or opposites attract? Patterns of spatial segregation and association among crested penguin populations during winter - Norman Ratcliffe; Sarah Crofts; Ruth Brown; Alastair M. M. Baylis; Stacey Adlard; Catharine Horswill; Hugh Venables; Phil Taylor; Philip N. Trathan; Iain J. Staniland (Journal of Biogeography, 2014)
Aim Competition for food among populations of closely related species and conspecifics that occur in both sympatry and parapatry can be reduced by interspecific and intraspecific spatial segregation. According to predictions of niche partitioning, segregation is expected to occur at habitat boundaries among congeners and within habitats among conspecifics, while negative relationships in the density of species or populations will occur in areas of overlap. We tested these predictions by modelling the winter distributions of two crested penguin species from three colonies in the south‐western Atlantic. Location Penguins were tracked from two large colonies on the Falkland Islands and one in South Georgia, from where they dispersed through the South Atlantic, Southern Ocean and south‐eastern Pacific. Methods Forty macaroni penguins ( Eudyptes chrysolophus ) from South Georgia and 82 southern rockhopper penguins ( Eudyptes chrysocome chrysocome ) from two colonies in the Falkland Islands were equipped with global location sensors which log time and light, allowing positions to be estimated twice‐daily, from April to August in 2011. Positions were gridded and converted into maps of penguin density. Metrics of overlap were calculated and density was related to remote‐sensed oceanographic variables and competitor density using generalized additive models. Results Macaroni penguins from western South Georgia and southern rockhopper penguins from Steeple Jason Island, Falkland Islands, were spatially segregated by differences in their habitat preferences thus supporting our first prediction regarding interspecific segregation. However, southern rockhopper penguins from Beauchêne Island showed a marked spatial overlap with macaroni penguins as the two had similar habitat preferences and strong mutual associations when controlling for habitat. Contrary to our predictions relating to intraspecific segregation, southern rockhopper penguins from Beauchêne Island and Steeple Jason Island were segregated by differences in habitat selection. Main conclusions Morphological differentiation probably allows macaroni penguins from South Georgia and southern rockhopper penguins from Beauchêne Island to coexist in areas of spatial overlap, whereas segregation of the two Falkland rockhopper penguin populations may have arisen from two distinct lineages retaining cultural fidelity to ancestral wintering areas.

Temperature explains variable spread rates of the invasive woodwasp Sirex noctilio in the Southern Hemisphere - M. Victoria Lantschner; José M. Villacide; Jeffrey R. Garnas; Philip Croft; Angus J. Carnegie; Andrew M. Liebhold; Juan C. Corley (Biological Invasions, 2014)

Spatial proximity loggers for recording animal social networks: consequences of inter-logger variation in performance - N. K. Boyland; R. James; D. T. Mlynski; J. R. Madden; D. P. Croft (Behavioral Ecology and Sociobiology, 2013)

Laboratory and field evaluation of fungicides for the management of sugarcane smut caused by Sporisorium scitamineum in seedcane - Shamsul A. Bhuiyan; Barry J. Croft; Rebecca S. James; Mike C. Cox (Australasian Plant Pathology, 2012)

The effect of d,l-methamphetamine on simulated driving performance - Beata Y. Silber; Rodney J. Croft; Luke A. Downey; David A. Camfield; Katherine Papafotiou; Phillip Swann; Con Stough (Psychopharmacology, 2012)

Testing a candidate parasitoid in the glasshouse: control efficacy of Aphaereta debilitata (Hymenoptera: Braconidae) against shore fly populations - Luke A. N. Tilley; Pat Croft; Peter J. Mayhew (BioControl, 2011)

The effect of sleep deprivation on BOLD activity elicited by a divided attention task - Melinda L. Jackson; Matthew E. Hughes; Rodney J. Croft; Mark E. Howard; David Crewther; Gerard A. Kennedy; Katherine Owens; Rob J. Pierce; Fergal J. O’Donoghue; Patrick Johnston (Brain Imaging and Behavior, 2011)

Multiseason evaluation of the MM5, COAMPS and WRF over southeast United States - Duanjun Lu; L. White; R. S. Reddy; Quinton L. Williams; Paul J. Croft (Meteorology and Atmospheric Physics, 2011)

ERP correlates of response inhibition after-effects in the stop signal task - Daniel J. Upton; Peter G. Enticott; Rodney J. Croft; Nicholas R. Cooper; Paul B. Fitzgerald (Experimental Brain Research, 2010)

Isolation and identification of cytoskeleton-associated prolamine mRNA binding proteins from developing rice seeds - Andrew J. Crofts; Naoko Crofts; Julian P. Whitelegge; Thomas W. Okita (Planta, 2010)

Acute dopamine and/or serotonin depletion does not modulate mismatch negativity (MMN) in healthy human participants - Sumie Leung; Rodney J. Croft; Valérie Guille; Kirsty Scholes; Barry V. O’Neill; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2010)

Patients with prostate cancer are less likely to develop oesophageal adenocarcinoma: could androgens have a role in the aetiology of oesophageal adenocarcinoma? - Sheldon C. Cooper; Stacey Croft; Rosie Day; Catherine S. Thomson; Nigel J. Trudgill (Cancer Causes & Control, 2009)

New Data on Miocene Neotropical Provinciality from Cerdas, Bolivia - Darin Andrew Croft; Federico Anaya; David Auerbach; Carmala Garzione; Bruce J. MacFadden (Journal of Mammalian Evolution, 2009)

Behavioural trait assortment in a social network: patterns and implications - Darren P. Croft; Jens Krause; Safi K. Darden; Indar W. Ramnarine; Jolyon J. Faria; Richard James (Behavioral Ecology and Sociobiology, 2009)

Evidence for modulation of facial emotional processing bias during emotional expression decoding by serotonergic and noradrenergic antidepressants: an event-related potential (ERP) study - Rebecca Kerestes; Izelle Labuschagne; Rodney J. Croft; Barry V. O’Neill; Zubin Bhagwagar; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2009)

Phylogenetic placement of the sugarcane orange rust pathogen Puccinia kuehnii in a historical and regional context - K. S. Braithwaite; B. J. Croft; R. C. Magarey; T. Scharaschkin (Australasian Plant Pathology, 2009)

RISK‐SENSITIVE ANTIPREDATOR BEHAVIOR IN THE TRINIDADIAN GUPPY, POECILIA RETICULATA - M. S. Botham; R. K. Hayward; L. J. Morrell; D. P. Croft; J. R. Ward; I. Ramnarine; J. Krause (Ecology, 2008)
The comparative approach has become a powerful tool for understanding how predation has shaped prey behavior. In this study we recorded the occurrence of common aquatic predator species and their densities in seven natural populations of Trinidadian guppies, Poecilia reticulata . We then exposed shoals of guppies from each of these populations to a series of predator treatments. Predator treatments differed in the species of predator used (pike cichlids, Crenicichla frenata ; rivulus, Rivulus hartii ; and freshwater prawns, Macrobrachium carcinus ) and thus in the level of risk posed. We recorded the antipredator responses of guppies in each of these predator treatments. The strength of antipredator behavior shown by guppies was affected by both the type of predator they were exposed to and the level of predation risk they experienced naturally in the wild. Importantly, we found that guppies from high‐risk populations showed a heightened response, compared to those from lower risk populations, only when exposed to the predator species that posed the greatest risk. Our results show the importance of individual predator species in shaping the behavioral traits of prey species at the population level. This has implications for prey movement between habitats that are geographically close but differ greatly in predator fauna.

D1-arginine257 mutants (R257E, K, and Q) of Chlamydomonas reinhardtii have a lowered QB redox potential: analysis of thermoluminescence and fluorescence measurements - Stuart Rose; Jun Minagawa; Manfredo Seufferheld; Sean Padden; Bengt Svensson; Derrick R. J. Kolling; Antony R. Crofts; Govindjee (Photosynthesis Research, 2008)

Genetic variability of genome segments 3 and 9 of Fiji disease virus field isolates - Junxi Jiang; Andrew W. Ridley; Herman Tang; Barry J. Croft; Karyn N. Johnson (Archives of Virology, 2008)

Acute high-dose glycine attenuates mismatch negativity (MMN) in healthy human controls - Sumie Leung; Rodney J. Croft; Barry V. O’Neill; Pradeep J. Nathan (Psychopharmacology, 2008)

Sugarcane smut in Queensland: arrival and emergency response - B. J. Croft; R. C. Magarey; P. G. Allsopp; M. C. Cox; T. G. Willcox; B. J. Milford; E. S. Wallis (Australasian Plant Pathology, 2008)

Social network theory in the behavioural sciences: potential applications - J. Krause; D. P. Croft; R. James (Behavioral Ecology and Sociobiology, 2007)

High-dose glycine inhibits the loudness dependence of the auditory evoked potential (LDAEP) in healthy humans - Barry V. O’Neill; Rodney J. Croft; Sumie Leung; Chris Oliver; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2007)

Acute dopamine D1 and D2 receptor stimulation does not modulate mismatch negativity (MMN) in healthy human subjects - Sumie Leung; Rodney J. Croft; Torsten Baldeweg; Pradeep J. Nathan (Psychopharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Numerical simulation of sea and bay breezes in a weak shear environment - D. Lu; L. White; R. S. Reddy; P. J. Croft; J. M. Medlin (Meteorology and Atmospheric Physics, 2006)

Dopamine receptor stimulation does not modulate the loudness dependence of the auditory evoked potential in humans - Barry V. O’Neill; Rodney J. Croft; Sumie Leung; Valérie Guille; Matthew Galloway; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2006)

Phloem Alkaloid Tolerance Allows Feeding on Resistant Lupinus angustifolius by the Aphid Myzus persicae - Yasmin J. Cardoza; Shao Fang Wang; Jenny Reidy-Crofts; Owain R. Edwards (Journal of Chemical Ecology, 2006)

The acute effects of d-amphetamine and methamphetamine on attention and psychomotor performance - Beata Y. Silber; Rodney J. Croft; Katherine Papafotiou; Con Stough (Psychopharmacology, 2006)

Social structure and co-operative interactions in a wild population of guppies (Poecilia reticulata) - D. P. Croft; R. James; P. O. R. Thomas; C. Hathaway; D. Mawdsley; K. N. Laland; J. Krause (Behavioral Ecology and Sociobiology, 2006)

Recent advances in the molecular biology of Leifsonia xyli subsp. xyli , causal organism of ratoon stunting disease - S. M. Brumbley; L. A. Petrasovits; S. R. Hermann; A. J. Young; B. J. Croft (Australasian Plant Pathology, 2006)

Genetic uniformity of international isolates of Leifsonia xyli subsp. xyli , causal agent of ratoon stunting disease of sugarcane - A. J. Young; L. A. Petrasovits; B. J. Croft; M. Gillings; S. M. Brumbley (Australasian Plant Pathology, 2006)

Is the distribution of Fiji leaf gall in Australian sugarcane explained by variation in the vector Perkinsiella saccharicida ? - A. W. Ridley; K. Dhileepan; K. N. Johnson; P. G. Allsopp; K. A. Nutt; G. H. Walter; B. J. Croft (Australasian Plant Pathology, 2006)

Management of an incursion of sugarcane smut in Australia - B. J. Croft; K. S. Braithwaite (Australasian Plant Pathology, 2006)

Social defeat increases alcohol preference of C57BL/10 strain mice; effect prevented by a CCKB antagonist - A. P. Croft; S. P. Brooks; J. Cole; H. J. Little (Psychopharmacology, 2005)

An evaluation of the sensitivity of the standardised field sobriety tests to detect the presence of amphetamine - Beata Y. Silber; Katherine Papafotiou; Rodney J. Croft; Con K. K. Stough (Psychopharmacology, 2005)

The effects of dexamphetamine on simulated driving performance - B. Y. Silber; K. Papafotiou; R. J. Croft; E. Ogden; P. Swann; C. Stough (Psychopharmacology, 2005)

Assortative interactions and social networks in fish - D. P. Croft; R. James; A. J. W. Ward; M. S. Botham; D. Mawdsley; J. Krause (Oecologia, 2005)

Miltefosine (Impavido): the first oral treatment against leishmaniasis - H. Sindermann; S. L. Croft; K. R. Engel; W. Bommer; H. J. Eibl; C. Unger; J. Engel (Medical Microbiology and Immunology, 2004)

Chronic MDMA (ecstasy) use, cognition and mood - K. McCardle; S. Luebbers; J. D. Carter; R. J. Croft; C. Stough (Psychopharmacology, 2004)

Intra‐sexual preferences for familiar fish in male guppies - D. P. Croft; B. J. Arrowsmith; M. Webster; J. Krause (Journal of Fish Biology, 2004)
Male guppies Poecilia reticulata were observed to develop shoaling preferences for familiar males over a 12 day period, at which time they showed a clear preference for familiar over non‐familiar males.

Social networks in fish - J. Krause; D. Croft; R. James (Journal of Fish Biology, 2003)
Social network theory underwent rapid development in the 1970s by sociologists and was recently further refined by physicists. Network theory has been applied to systems consisting of interconnected components as different as that of actors in Hollywood, the neural network of the nematode worm Caenorhabditis elegans , and the US national power grid. Network theory has great potential as a conceptual tool, for example, it can be used to provide quantitative predictions regarding information transmission, spreading of diseases, and the potential for establishing reciprocal altruistic relationships. Conventionally behavioural studies have been restricted to the analysis of social interactions between isolated pairs or small groups of individuals. Here we built up, however, from pair‐wise interactions, the social network of an entire population of guppies ( Poecilia reticulata ) in Trinidad. We show that guppies have highly structured social networks with significant repeated interactions between male–male, female–female and male–female pairs. Furthermore, sexual segregation within the network is positively correlated with the strength of the social interactions. Finally, individuals were observed to be more variable in their inter‐sexual interactions than their intra‐sexual ones.

Comparison of a Commercial Reversed Passive Latex Agglutination Assay to an Enzyme Immunoassay for the Detection of Shiga Toxin-Producing Escherichia coli - K. C. Carroll; K. Adamson; K. Korgenski; A. Croft; R. Hankemeier; J. Daly; C. H. Park (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Report of the VIIth ISSCT Pathology Workshop Louisiana, USA 11–16 May, 2003 - Philippe Rott; Jack C. Comstock; Barry J. Croft; Anusorn Kusalwong; Salem Saumtally (Sugar Tech, 2003)

Sex-biased movement in the guppy ( Poecilia reticulata ) - Darren P. Croft; Brett Albanese; Bethany J. Arrowsmith; Marc Botham; Michael Webster; Jens Krause (Oecologia, 2003)

The use of a ‘phantom scalp’ to assess the possible direct pickup of mobile phone handset emissions by electroencephalogram electrode leads - A. W. Wood; D. L. Hamblin; R. J. Croft (Medical & Biological Engineering & Computing, 2003)

When fish shoals meet: outcomes for evolution and fisheries - Darren P Croft; Jens Krause; Iain D Couzin; Tony J Pitcher (Fish and Fisheries, 2003)
The mechanisms underlying the social structure of free‐ranging fish shoals have received little attention in comparison to functional studies on shoaling. Recently, however, a number of investigations, both in the marine and in the freshwater environment, have begun to address the underlying mechanisms by concentrating on interactions between free‐ranging shoals. The rates of shoal encounters can influence the opportunities for individual assortment by phenotype and selection of shoal size; act as a constraint on the observed patterns of shoal structure by restricting individual choice behaviour and were found to be high in several small freshwater species (where intershoal distances were small), but lower in marine species where shoals were more dispersed. The duration of encounters may play a role in that it affects both the time available for assessment (of the encountered shoal) as well as that for exchange of individuals. Scarce published information on the outcome of shoal encounters suggests that the outcome of shoal encounters is influenced by shoal composition but not by shoal size. Individual behaviour may have evolved to maintain shoal size when shoals encounter, but when fish populations are depleted by fishing, this trait can exacerbate range and stock collapse. Furthermore, an understanding of the dynamics of shoal encounters has important consequences for the evolution of reciprocal altruism and the transmission of information through social learning within populations. Finally, information on encounter rates between shoals and the number of individuals that are exchanged on such occasions could be important for making predictions about the spread of disease through fish populations.

Macronuclear Molecules Encoding Actins in Spirotrichs - Katie E. Croft; Andrew B. Dalby; Daniel J. Hogan; Kindra E. Orr; Elizabeth A. Hewitt; Robert J. Africa; Michelle L. DuBois; David M. Prescott (Journal of Molecular Evolution, 2003)

Development of PCR-based markers for detection of Leifsonia xyli subsp. xyli in fibrovascular fluid of infected sugarcane plants - P. W. J. Taylor; L. A. Petrasovits; R. Van der Velde; R. G. Birch; B. J. Croft; M. Fegan; G. R. Smith; S. M. Brumbley (Australasian Plant Pathology, 2003)

Seasonal aggregations of Canadian east coast pollock as inferred from the commercial fishery and hydroacoustic observations - J. D. Neilson; L. Annis; P. Perley; A. Clay; C. Croft; M. O'Connor (Journal of Fish Biology, 2002)
Data from an otter trawler fleet fishing on the Scotian Shelf combined with year‐round hydroacoustic data indicated that the locations of aggregations of pollock Pollachius virens did not change appreciably from month to month. The proportion of pollock mass compared with total catch mass in individual trawl catches, however, tended to be higher from September to February. The period of highest catch rates was shown to be the December to January period. This period coincided with the period when pollock had the least affinity with the seabed based on information from hydroacoustic observations, a behavioural consideration for acoustic survey design. Based on these observations, it was concluded that the optimal time to conduct an acoustic survey was during the December to January period.

Population differentiation of Potamogeton pectinatus in the Baltic Sea with reference to waterfowl dispersal - R. A. King; R. J. Gornall; C. D. Preston; J. M. Croft (Molecular Ecology, 2002)
Forty populations of Potamogeton pectinatus L. were sampled from around the Baltic Sea basin. Analysis of 62 ISSR ‘loci’ showed that the number of clones per population is very variable but shows a tendency to decrease with latitude. Analysis of molecular variance revealed that, overall, just over half the variability is stored within populations and just under half between them (φ ST 0.496). In pairwise comparisons, most populations are significantly differentiated. Genetic distance between populations, as measured by φ ST , increases with geographical distance. Levels of population differentiation, however, are lower on the southeastern Swedish coast than elsewhere, a reduction correlated with the importance of this area as a staging post for the massive migrations of waterfowl from arctic Russia and western Siberia. Cumulative plots of φ ST against geographical distance along this coast suggest that, although it does not prevent significant population differentiation, bird traffic reduces it over distances of 150–200 km.

A grid‐net technique for the analysis of fish positions within free‐ranging shoals - D. J. Hoare; A. J. W. Ward; I. D. Couzin; D. P. Croft; J. Krause (Journal of Fish Biology, 2001)
The design and operation of a grid‐net are described, which allows the capture of entire shoals of wild fish and preserves information about the two‐dimensional structure of shoals and the spatial positions of individual fish within the shoal. This simple technique facilitates investigation of several aspects of individual differences in fish shoaling behaviour in the wild for the first time.

Jerking in predaceous mites (Acari: Phytoseiidae) with emphasis on larvae - J. Scott Blackwood; Brian A. Croft; Peter Schausberger (Experimental and Applied Acarology, 2001)

The relative contributions of ecstasy and cannabis to cognitive impairment - Rodney J. Croft; Alex J. Mackay; Alex T.D. Mills; John G.H. Gruzelier (Psychopharmacology, 2001)

Molecular polymorphism and phenotypic variation in Aspergillus carbonarius - Ferenc Kevei; Zsuzsanna Hamari; Jnos Varga; Zofia Kozakiewicz; James H. Croft (Antonie van Leeuwenhoek, 1996)

Larval morphology and development of the parasitoidDacnusa sibirica [Hym.: Braconidae] in the leafminer hostChromatomyia syngenesiae - P. Croft; M. J. W. Copland (BioControl, 1994)

Biological control ofAphis pomi [Hom.: Aphididae] ofAphidoletes aphidimyza [Dip.: Cecidomyiidae]; a predator-prey model - J. G. Morse; B. A. Croft (BioControl, 1987)

Developed resistance to azinphosmethyl in a predator-prey mite system in greenhouse experiments - J. G. Morse; B. A. Croft (BioControl, 1981)

Research advances on pesticide resistance in natural enemies - B. A. Croft; J. G. Morse (BioControl, 1979)